A baseline constrained LAMBDA method for integer ambiguity resolution of GNSS attitude systems. - Teunissen, Peter; Park, C. (2008)
In this paper, an efficient integer ambiguity resolution method for GNSS attitude determination system is described. The proposed method solves the integer least-squares with quadratic equality constraints(ILSQE) problem and shows an expansion of the LAMBDA method can be used to solve it. The solution of ILSQE is shown and an efficient implementation with a LAMBDA based method is given. The method is compared with some other methods. The results of static and dynamic tests show the dramatic improvement of the success rates of integer ambiguity resolution.